Pemahaman Hadis Doa Pengalihan Hujan Pendekatan Geografis Jakarta menurut Ali Mustafa Yaqub - Fatihunnada Anis; Afaf Nazrat Uyun (ILMU USHULUDDIN, 2020)
This article will explain and analyze Ali Mustafa Yaqub’s hadith understanding on the hadith of transferring a heavy rain with a geographical approach. The author observes that there are still many problems of misunderstanding on this type of hadith that are apparent among Indonesian Muslim communities, especially the citizen of Jakarta when facing heavy rains and floods in early 2020. The geography science is not a source of Islamic law, but this science can be one of the instruments on understanding the hadith correctly. Based on the geomorphology of geography, the hadith prayer for transferring a heavy rain cannot be practiced by the Jakarta residents because that prayer will only cause floods in Jakarta due to heavy rain that came down in Bogor and return to Jakarta. Ali Mustafa offered a prayer for the citizens of Jakarta when facing heavy rain with the phrase "O Allah, send down a rain at the sea, not to us and around us". This kind of understanding is only applicable to the residents of Jakarta and other cities that have a form of land like Jakarta like Bekasi.  For the cities which have landforms like Madinah can recite the prayer because it was indeed recited by the Prophet when heavy rains and floods occurred in the Medina.